Sustainable Production of Bioplastics from Lignocellulosic Biomass: Technoeconomic Analysis and Life-Cycle Assessment - Kim, Hyunwoo; Lee, Shinje; Ahn, Yuchan; Lee, Jinwon; Won, Wangyun (ACS sustainable chemistry & engineering, 2020)
2,5-Furandicarboxylic acid (FDCA), an eco-friendly biobased material, can replace petroleum-based terephthalic acid (TPA), in the polymer industry, for applications such as water bottle production and food packaging. In this study, an integrated process was developed for the coproduction of FDCA as a biobased plastic monomer and 1,5-pentanediol as a high-value product from lignocellulosic biomass using catalytic conversions and designing separation areas. The integrated process has several energy-intensive units that require a considerable amount of heating sources. Heat integration is performed to reduce and satisfy total heating requirements. Through a technoeconomic analysis, the minimum selling price of FDCA is determined to be US$1024/ton. Moreover, a wide range of sensitivity analyses are conducted to identify the major cost drivers among the economic and environmental parameters. Environmental impacts are compared between biomass-derived FDCA and petroleum-derived TPA productions by life-cycle assessment. In the former production, fossil depletion is lower (53%) than that of the latter production, although climate change of the former is higher (29%) than that of the latter. FDCA production can be more environmentally friendly by changing the sources for electricity generation.